Pemanfaatan Integrasi Nilai Budaya: Analisis Bahan Ajar Bipa Terbuka - Ilawati Ilawati; Laily Nurlina (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The utilization of cultural value integration in open BIPA (Indonesian for Foreign Speakers) teaching materials is a strategic approach that can improve the quality of Indonesian language learning among foreign speakers. This study aims to analyze the utilization of cultural value integration in open Indonesian for Foreign Speakers (BIPA) teaching materials. This method is carried out by collecting ten scientific articles in Indonesian language journals found from the Google Scholar database. The literature comes from the period 2021 - 2024. This study explores various relevant scientific articles to identify effective methods and media in integrating cultural values ​​into BIPA teaching. From the ten articles analyzed, the results show that the use of cultural elements, such as folklore, traditions, and social practices, in teaching materials not only enriches learning content but also helps learners understand the social and cultural context in which the language is used. This creates a more contextual and in-depth learning experience, which in turn improves learners' communication skills. These findings provide recommendations for the development of BIPA teaching materials that are more comprehensive and responsive to the needs of foreign learners.